Transisi menuju Demokrasi di Indonesia - Rafni, Al (Pusat Kajian Civics Fakultas Ilmu-ilmu Sosial Universitas Negeri Padang, 2002)
At this time, Indonesia is in transition era head for democracy. This process has moved to â€œuncompleted replacementâ€ following the fall of Neo-patrimonial regime that was ruling for more than three decades. Many of complicated problems has raised by this era, such as disintegration, mass euphoria, segregation elite, parliamentary â€œnoiseâ€, as well as many kinds of conflict among political parties which hit with the fist in anger. All above become sensitive points that are decisive factors for whether Indonesia will become democratic or not in the future. Key Words: Transisi, Demokrasi